Effect Of Shear Wall Position Variations On The Seismic Response Of Reinforced Concrete Buildings: A Case Study Of Ristia Resort - Putu Didik Sulistiana; I Gede Premananda Putra; Cokorda Agung Yujana; Anak Agung Sagung Dewi Rahadiani (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2026)
The arrangement of shear walls plays a fundamental role in controlling the seismic behavior of reinforced concrete buildings by affecting lateral stiffness and structural deformation during earthquake loading. This study investigates the seismic performance of the Ristia Resort reinforced concrete building subjected to three alternative shear wall layouts. Three numerical structural models with identical geometry, material properties, loading conditions, and seismic design parameters were developed, with the shear wall locations defined as the only variable. Seismic performance was evaluated through response spectrum analysis based on SNI 1726:2019. The evaluation considered inter-story drift, story stiffness, and the proportion of design base shear carried by the shear wall system. Among the investigated configurations, Model 1 achieved the best structural performance by reducing the third-floor inter-story drift by 10.69% and 11.19% relative to Models 2 and 3, respectively. It also increased the average X-direction story stiffness by 6.38% and 6.48%, while the shear wall system resisted 66.74% and 71.08% of the design base shear in the X- and Y-directions, respectively. These results demonstrate that a symmetrical shear wall arrangement provides a more efficient lateral load-resisting system and improves the overall seismic performance of reinforced concrete buildings.